Tuberculosis in the twentieth century: time-series mortality in São Paulo, Brazil, 1900-97 A tuberculose através do século: séries temporais para a mortalidade em São Paulo, Brasil, 1900-97 - José Leopoldo Ferreira Antunes; Eliseu Alves Waldman (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1999)
The objective of this study was to characterize tuberculosis mortality trends in the Municipality of São Paulo, Brazil, from 1900 to 1997. Standardized tuberculosis mortality rates and proportional mortality ratios were calculated and stratified by gender and age group based on data provided by government agencies. These measures were submitted to time-series analysis. We verified distinct trends: high mortality and a stationary trend from 1900 to 1945, a heavy reduction in mortality (7.41% per year) from 1945 to 1985, and a resumption of increased mortality (4.08% per year) from 1985 to 1995. In 1996 and 1997 we observed a drop in tuberculosis mortality rates, which may be indicating a new downward trend for the disease. The period from 1945 to 1985 witnessed a real reduction in tuberculosis, brought about by social improvements, the introduction of therapeutic resources, and expansion of health services. Recrudescence of tuberculosis mortality from 1985 to 1995 may reflect the increasing prevalence of Mycobacterium and HIV co-infection, besides loss of quality in specific health programs. Com o objetivo de caracterizar tendências da mortalidade por tuberculose no Município de São Paulo, Brasil, 1900-1997, foram calculados e estratificados por gênero e grupo etário os coeficientes padronizados de mortalidade e as razões de mortalidade proporcional, por intermédio de dados providos por agências governamentais. Esxas medidas foram ainda submetidas à análise de séries temporais. Foram verificadas diferentes tendências: de 1900 a 1945, alta mortalidade e tendência estacionária; de 1945 a 1985, forte redução na mortalidade (7,41% por ano); e de 1985 a 1995, retomada do crescimento da mortalidade (4,08% por ano). Em 1996 e 1997, a redução observada nos coeficientes de mortalidade pode estar indicando um novo perfil descendente para a enfermidade. Os anos de 1945 a 1985 marcaram período de acentuada queda para a tuberculose, produzida por melhorias sociais, pela introdução de recursos terapêuticos e pela ampliação da cobertura dos serviços de saúde. O recrudescimento da tuberculose, de 1985 a 1995, pode estar refletindo a crescente prevalência da co-infecção por Mycobacterium e por HIV, além da virtual perda de qualidade em programas específicos de controle da endemia.